Determinant Factors of Regional Inflation in Decentralized Indonesia - Brodjonegoro, Bambang P. S.; Simorangkir, Iskandar; Gitaharie, Beta Y.; Falianty, Telissa (Institute for Economic and Social Research, 2005)
.